MAKNA KIDUNG WARGASARI - Wira Putra, I Made Arik (Humanis; Volume 5. No. 1. Oktober 2013)
This study titled kidung wargasari analysis of semiotic. Purpose of this study was to describe the meaning contained in the text. Methods and techniques in this study can be divided into three stages, namely: 1) stage providing data using the method of reading and interviews, supported by a technique of recording and translation, 2) stage of data analysis using descriptive analytic methods, supported by using deductive and inductive techniques, and (3) the presentation of the results of the data analysis stage usingformal and informal methods, supported by deductive and inductive techniques. Research results in this the unfolding of the meaning contained in the text songs wargasari.
Keywords: kidung, warga sari, semiotic, and meaning